A Review of KRAS Inhibitors and Potential Improvement in The Future - Jiang, Ziyan (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Kirsten rat sarcoma viral (KRAS) oncogene is one of the most common mutant genes in tumors, especially in non-small cell lung cancer, colorectal cancer, and pancreatic cancer. In recent years, great success was achieved in targeting KRAS for the treatment of tumors. So far, two drugs, sotorasib and adagrasib, have gotten through the accelerated approval by the FDA. Even so, current treatments are still far from satisfaction due to the inevitable acquired drug resistance and the diversity of mutant isoforms. Various approaches are being investigated to address these issues, including the combination of multiple medications and the development of drugs with more targets. Overall, targeting KRAS is a promising and effective strategy for the treatment of cancer. For this reason, the article aims at introducing several representative KRAS-targeting drugs and exhibiting the latest research progress. Discussions about the acquired resistance and the potential solutions are also included, hoping to provide inspiration for the development and improvement of new drugs.